Sex Differences in Obesity and Cognitive Function in Chinese Elderly Patients With Chronic Schizophrenia - Li, Wei; Lin, Sun; Yue, Ling; Fang, Yuan; Xiao, Shifu (Frontiers in Endocrinology, 2022)
Abstract Background It is well known that schizophrenia is associated with sex differences. However, no study has explored the sex differences in obesity and cognitive function in elderly Chinese patients with schizophrenia. Objective This study aimed to compare sex differences in obesity and cognitive function in elderly Chinese individuals with schizophrenia. Methods We recruited 304 elderly Chinese patients and collected their demographic, clinical, and lipid parameters. The Montreal Cognitive Assessment (MoCA) was used to assess the global cognitive functions of the participants, while the Positive and Negative Syndrome Scale (PANSS) was used to assess psychopathological symptoms. Results The prevalence of obesity in men and women was 11.7% (19/163) and 21.3% (30/141), respectively. The score (14.51±6.504) of MOCA in elderly male patients with schizophrenia was significantly higher than that (11.40±6.822) in female patients. There was a positive correlation between the MOCA scores and body mass index (BMI) (r=0.211, p=0.016) in male elderly patients with schizophrenia. Conversely, the MOCA scores of female elderly patients with schizophrenia did not correlate with BMI (p>0.05). The results of linear regression analysis showed that the BMI of elderly patients with schizophrenia was related to diabetes mellitus (T=3.192, p=0.002, 95% CI: 0.923-3.930) in women and fasting blood glucose (T=2.912, p=0.004, 95% CI: 0.243-1.267) in men. Conclusions Our findings suggest that there are significant sex differences in obesity and cognitive function. Elderly Chinese patients with schizophrenia, and obesity increases the risk of abnormal glucose metabolism in both men and women with schizophrenia. Keywords: Elderly; Obesity; Schizophrenia; Chinese; Cognitive impairment; Sex difference